The EU Regional Social Progress Index 2.0 - De Dominicisi, Laura,Cabeza Martinez, Begoña,Kovacic, Matija,Papadimitriou, Eleni (Publications Office of the European Union, 2024)
Measuring economic development beyond GDP is of paramount importance for fostering regional cohesion, promoting inclusive growth, and advancing sustainable development. Therefore, there is a growing emphasis in the European Union on incorporating alternative metrics that offer a more comprehensive assessment of progress and well-being across EU regions. Against this backdrop, the EU regional Social Progress Index (EU-SPI) has proved to be a valuable tool, complementing traditional economic indicators by capturing a broader range of social factors contributing to well-being. The 2024 edition of the EU-SPI seeks to improve the previous editions of the index making it an even more powerful tool in measuring social progress across EU regions in its many dimensions.
10.2776/786554
Keywords: Graue Literatur; EU regional policy; competitiveness; economic indicator; economic statistics; nomenclature